If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6y = -19 Solving 5x + -6y = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 5x + -6y + 6y = -19 + 6y Combine like terms: -6y + 6y = 0 5x + 0 = -19 + 6y 5x = -19 + 6y Divide each side by '5'. x = -3.8 + 1.2y Simplifying x = -3.8 + 1.2y
| 1x-41=3 | | -2(v+2)=2v-4+2(3v+1) | | T-19=17 | | 72x+16=64x+40 | | -119=3(3-4x)-4x | | .20x+8=13 | | 15+8v=8v-3(v-3) | | -4(-6c+7)=35 | | 2x+35+5x+5=180 | | .25x+7=9 | | 5x+5+2x+35=90 | | 4x^3-7x^2-5x-6= | | b+1-3b=(4+6b)-7 | | -7n+10+9n=18 | | 5x+5+2x+35=180 | | 6x-3=6x+11 | | -7n+10+9n=18 | | 5x+5+2x+35=180 | | -7n+10+9n=18 | | -7n+10+9n=18 | | -173=7+4(7k-3) | | 6y+3x=32 | | 150+35x=45 | | 30=-4a+10 | | ax-6=t | | -10h(h-2)-4=36 | | H=297+-4.4t | | q+r=37 | | -2a+5=19 | | 34-(-4)=x | | 46=2x+4x+4 | | -2(7w-2)+5w=2+2(3w-8) |